Commercial real estate restructuring revolution strategies, tranche warfare, and prospects for recovery - Meister, Stephen B. (Wiley finance series., 2011)
"How to plan for the commercial real estate collapse Encompassing apartment, office, retail, hospitality, warehouse, manufacturing, and flex or R & D buildings, commercial real estate (CRE) investment in the U.S. totaled $6.4 trillion at the end of 2008. As noted in the February 2010 Congressional Oversight Panel Report, $1.4 trillion of CRE debt is coming due by 2014 and half of the CRE projects securing such debt are underwater. Commercial Real Estate Restructuring Revolution: Strategies, Tranche Warfare, and Prospects for Recovery looks at how we got into this mess-impacts of the housing crisis, debt structures, lender-borrower collusion, and bankruptcy abuses-and offers possible solutions to the CRE crisis. Along the way, author Stephen Meister: Discusses how CRE value losses are being driven by investors' risk adjusted cap rates, not just poorer market fundamentals. Discusses strategies and emerging trends in CRE foreclosures, including forced lender fundings, lender attempts to chill bids and UCC foreclosure tactics and pitfalls. Proposes legislative solutions and explains how any rebound will require federal spending cuts, a vast deleveraging and a market clearing process. With a crashing CRE debt market and the hundreds of CRE-heavy regional banks destined for failure, getting out ahead of the curve is essential. Commercial Real Estate Restructuring Revolution addresses how we got here and how you can plan for the impending crash"--